New perspectives on individual differences in language learning and teaching - Pawlak, Mirosław (Second Language Learning and Teaching, 2012)
The volume constitutes an attempt to capture the intricate relationship between individual learner differences and other variables which are of interest to theorists, researchers and practitioners representing such diverse branches of applied linguistics as psycholinguistics, sociolinguistics, pragmatics or language teaching methodology. It brings together contributions by Polish and international authors, including leading experts in the field, touching upon changing perspectives on individual variation, cognitive, affective and social variables, learning deficits as well as their impact on learning and teaching. It offers a multifaceted perspective on these problems and shows how theory and research can be translated into classroom practice.